Teaching Content Using English as a Medium of Instruction at Universities in Vietnam: Issues and Solutions (Asian Education Studies, 2018)
In the globalization era, English is becoming the official international language. This originates from the importance of English in the stages of integration, internationalization, and globalization. English is the language of computer science, economics, science, and technology. Actually, future Vietnamese scientists not only need to grasp the knowledge of their specializations in the Vietnamese language but also to be able to expand the international relationships with their foreign counterparts and take advantage of opportunities for joining scientific projects with their colleagues from developed countries, so that they can contribute to the global achievements of science. For that, they need to possess a good command of the English language. For aforementioned reasons, English should be used as the medium language for content instruction at Vietnamese universities. Using English as a Medium of Instruction (EMOI) becomes a necessity at Vietnamese universities on a large scale. In terms of majors and schools, priority can be given to such fields as industry, economics, technology, and natural sciences.